2021
DOI: 10.1111/mec.16067
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of altitude‐associated wing shape in two tropical butterflies

Abstract: Climate change is forcing organisms to "move, adapt, or die". With temperatures rising and land-use changing in the lowlands, shifting to higher elevations might be the only way to flee extinction for many taxa (Chen et al., 2011). However, the environment changes drastically along mountains, with diverse sets of challenges expected to drive local adaptation (Halbritter et al., 2015). Thus, identifying the genomic mechanisms that allow organisms to inhabit wide ranges is key to understanding which taxa are mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…The two subspecies occasionally hybridize in a narrow transition zone associated with a strong (wet/dry) environmental gradient. Recent work of Montejo‐Kovacevich et al ( 2019 ), Montejo‐Kovacevich et al ( 2022 ), Montejo‐Kovacevich, Salazar, et al ( 2021 ) and Meier et al ( 2021 ) showed the effects of elevation gradient in shaping wing morphology and genetic local adaption in H. erato and H. melpomene . In this context, our study further highlights the role that the environment can play in shaping local populations and contribute to species formation.…”
Section: Discussionmentioning
confidence: 99%
“…The two subspecies occasionally hybridize in a narrow transition zone associated with a strong (wet/dry) environmental gradient. Recent work of Montejo‐Kovacevich et al ( 2019 ), Montejo‐Kovacevich et al ( 2022 ), Montejo‐Kovacevich, Salazar, et al ( 2021 ) and Meier et al ( 2021 ) showed the effects of elevation gradient in shaping wing morphology and genetic local adaption in H. erato and H. melpomene . In this context, our study further highlights the role that the environment can play in shaping local populations and contribute to species formation.…”
Section: Discussionmentioning
confidence: 99%
“…The wing area (WA) was measured by drawing the contour of the forewing, starting and ending at the tegula ( Figure 1 b). After summarizing the relevant literature, we found that the wing loading (WL) and wing aspect ratio (WAR) also have a certain relationship with altitude[ 13 , 57 ]. Since it is difficult to obtain accurate body mass data on parasitoids, the WL was replaced by MEL 3 /WA 2 [ 58 ], and the WAR was evaluated by FL 2 /WA [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, SNPs in close proximity often exhibit correlated patterns of association due to their nonindependent inheritance (genetic linkage). To leverage this linkage information, recent approaches have aggregated data across multiple adjacent sites through the use of window-based analyses ( 85 , 86 ). These approaches have the advantage of increasing statistical power and improving the signal-to-noise ratio ( 29 ).…”
Section: Methodsmentioning
confidence: 99%